2002
DOI: 10.1103/physrevb.65.132416
|View full text |Cite
|
Sign up to set email alerts
|

Cooling-rate dependence of the antiferromagnetic domain structure of a single-crystal charge-ordered manganite

Abstract: The low temperature phase of single crystals of Nd0.5Ca0.5MnO3 and Gd0.5Ca0.5MnO3 manganites is investigated by squid magnetometry. Nd0.5Ca0.5MnO3 undergoes a charge-ordering transition at TCO=245K, and a long range CE-type antiferromagnetic state is established at TN =145K. The dc-magnetization shows a cooling rate dependence below TN , associated with a weak spontaneous moment. The associated excess magnetization is related to uncompensated spins in the CE-type antiferromagnetic structure, and to the presenc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Very recently, Mathieu et al reported that MFC under 20 Oe in Nd0.5Ca0.5MnO3 exhibits the different relaxation effect in the typical characteristic time of ∼ 10 2 second by changing only the cooling rate. 37 Moreover, the difference of MFC in the history of the cooling rate increases with time. Based on these studies, we have done following THz-TDS experiments: We rapidly cooled the another sample used in Sec.…”
Section: Assignment and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Very recently, Mathieu et al reported that MFC under 20 Oe in Nd0.5Ca0.5MnO3 exhibits the different relaxation effect in the typical characteristic time of ∼ 10 2 second by changing only the cooling rate. 37 Moreover, the difference of MFC in the history of the cooling rate increases with time. Based on these studies, we have done following THz-TDS experiments: We rapidly cooled the another sample used in Sec.…”
Section: Assignment and Discussionmentioning
confidence: 99%
“…Therefore, we compare our experimental results to the typical characteristics of the PS in CO manganites. 35,36,37 Best example in the PS picture is the slow relaxation effect observed in Pr0.67Ca0.33MnO3 by Anane et al (Ref. 35) and Cr-doped manganites by Kimura et al, 36 in which the ferromagnetic fraction can be artificially controlled by H-annealing process and also the Cr (impurity)-doping at the Mn-site.…”
Section: Assignment and Discussionmentioning
confidence: 99%
“…However, no long-range ferromagnetic order of the Nd 3ϩ ions was found in neutron diffraction measurements at these low temperatures. 17,18 The increase in magnetization at low temperatures was associated by Mathieu et al 21 to a short-range magnetic ordering of the intrinsic magnetic moment of Nd 3ϩ ions. Nonetheless, a short-range magnetic ordering should not produce the Schottky-like anomaly.…”
Section: A Magnetization Measurementsmentioning
confidence: 91%
“…2,3,5,6 Presence of two ferromagnetic phases with different orbital order and electronic properties 3,4,7 leads to appearance of metastable states with markedly different resistivity. [8][9][10][11][12][13][14][15][16] Metastable states are characterized by history dependent conductivity, pronounced relaxation of magnetization and resistivity, memory effects in electric resistance and magnetization, and strong 1/f-type conductivity noise frequently accompanied by non-Gaussian fluctuations.…”
Section: Introductionmentioning
confidence: 99%